The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1039/d1en00788b
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic oxidative growth of goethite-coated sand particles in column reactors during 4-chloronitrobenzene reduction by Fe(ii)/goethite

Abstract: Reduction of nitroaromatic compounds (NACs), an important class of groundwater pollutants, by Fe(II) associated with iron oxides, a highly reactive reductant in anoxic aquifers, has been studied widely, but there...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 57 publications
3
11
0
Order By: Relevance
“…37 Our recent work showed that in the presence of Fe(II) and 4-ClNB, the reactivity of goethite-coated sand was dynamic due to changes in flow paths over time as oxidative mineral growth occurred. 38 Measurements of particles detached from the sand by TEM showed growth in particle length, similar to observations from batch studies. 5,39 The comprehensive study of the impact of NOM on reactivity, particularly in the context of reducing oxidized pollutants at the goethite surface in the presence of Fe(II), requires experiments using mineral-fractionated NOM.…”
Section: ■ Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…37 Our recent work showed that in the presence of Fe(II) and 4-ClNB, the reactivity of goethite-coated sand was dynamic due to changes in flow paths over time as oxidative mineral growth occurred. 38 Measurements of particles detached from the sand by TEM showed growth in particle length, similar to observations from batch studies. 5,39 The comprehensive study of the impact of NOM on reactivity, particularly in the context of reducing oxidized pollutants at the goethite surface in the presence of Fe(II), requires experiments using mineral-fractionated NOM.…”
Section: ■ Introductionsupporting
confidence: 73%
“…The uneven additional iron measured in the different zones is attributed to the reactant concentration gradient, with concentrations highest at the inlet (bottom). 38 For the column conditioned with SRFA, however, the concentration gradient was less steep because of the low reactivity of SRFA-treated particles (Figure 5c), which means that the distribution of reactants throughout the column was more similar from bottom to top, resulting in a more even distribution of new mineral growth.…”
Section: Acs Earth Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical analysis showed shard-like granules with a modal diameter of approximately 1.4 μm, though the larger particles, while fewer in number, contributed most to the mass of siderite in the reactors (Figure S1). Compositional analysis was done using inductively coupled plasma–optical emission spectroscopy (ICP-OES) following existing methods, described in the SI . Batch reactors were prepared by adding siderite powder into 37 mL serum bottles equipped with a magnetic stir bar.…”
Section: Methodsmentioning
confidence: 99%
“…Compositional analysis was done using inductively coupled plasma−optical emission spectroscopy (ICP-OES) following existing methods, described in the SI. 71 Batch reactors were prepared by adding siderite powder into 37 mL serum bottles equipped with a magnetic stir bar.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%